2021
DOI: 10.4254/wjh.v13.i8.949
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive tests for predicting liver outcomes in chronic hepatitis C patients: A systematic review and meta-analysis

Abstract: BACKGROUND Liver fibrosis leads to liver-related events in patients with chronic hepatitis C (CHC) infection. Although non-invasive tests (NITs) are critical to early detection of the development of liver fibrosis, the prognostic role of NITs remains unclear due to the limited types of NITs and liver outcomes explored in previous studies. AIM To determine the prognostic value of NITs for risk stratification in CHC patients. METHODS The protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(167 reference statements)
0
5
0
Order By: Relevance
“…Among serum biomarkers, APRI and FIB-4 are the most widely used for chronic liver diseases such as nonalcoholic liver disease (NAFLD) and viral hepatitis including HBV and HCV [ 32 , 33 , 34 ], and meta-analyses have also reported about AIH [ 35 , 36 ]. These two serum indicators are considered versatile because of their good reproducibility and high applicability, and they do not incur additional measurement costs [ 31 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among serum biomarkers, APRI and FIB-4 are the most widely used for chronic liver diseases such as nonalcoholic liver disease (NAFLD) and viral hepatitis including HBV and HCV [ 32 , 33 , 34 ], and meta-analyses have also reported about AIH [ 35 , 36 ]. These two serum indicators are considered versatile because of their good reproducibility and high applicability, and they do not incur additional measurement costs [ 31 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited data are available on serological markers assessed after SVR as predictors of portal hypertension decompensation. Boursier et al found that the dynamic course of FIB-4 after SVR was associated with the risk of developing any type of LRE [ 16 ], while Yongpisarn et al also reported FIB-4 after SVR to be a good predictor of the risk of developing LREs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Time-varying factors included cirrhosis diagnosis, duration since cirrhosis diagnosis, fibrosis-4 (FIB-4) score (and individual components of FIB-4), serum albumin, sodium, bilirubin, international normalized ratio, hemoglobin, hepatitis B virus surface antigen, diabetes, body mass index (BMI), hypertension, dyslipidemia, active alcohol use disorder, smoking status, and medical and mental health comorbidity. We defined cirrhosis based on ICD codes for cirrhosis or its complications recorded any time before baseline or the presence of FIB-4 > 3.25 (as defined below) (9). We used the date of first instance of cirrhosis code(s) as cirrhosis diagnosis date and once present they were presumed to have cirrhosis for the remaining follow-up time.…”
Section: Methodsmentioning
confidence: 99%
“…We defined cirrhosis based on ICD codes for cirrhosis or its complications recorded any time before baseline or the presence of FIB-4 . 3.25 (as defined below) (9). We used the date of first instance of cirrhosis code(s) as cirrhosis diagnosis date and once present they were presumed to have cirrhosis for the remaining follow-up time.…”
Section: Predictor Variablesmentioning
confidence: 99%